Developmental Environmentalism: State Ambition and Creative Destruction in East Asia's Green Energy Transition - Elizabeth Thurbon; Sung-Young Kim; Hao Tan; John A. Mathews (Oxford University Press, 2023)
Why has East Asia emerged as the global leader in green energy industries but—until recently—lagged on carbon emission reduction? What is new and distinctive about East Asia's approach to the green energy transition? And what does this approach mean for the world? This book provides the first comprehensive account of East Asia's green energy shift. Through an analysis of the ambitious national strategies of China and South Korea, the authors show how state actors have pursued a distinctively East Asian approach to transforming their energy systems, involving first the rapid creation of new green energy industries and then the coordinated destruction of fossil fuel incumbencies. This approach—described as 'developmental environmentalism'—is aimed at establishing East Asian economies as leaders in the green industries of the future, while at the same time addressing the pressing environmental, social, and political problems associated with the carbon-intensive industries of the past. To execute their analysis, the authors synthesize insights from cutting-edge Developmental State and Schumpeterian theorizing. They show how state actors in East Asia are engaging in a sophisticated kind of economic statecraft, strategically harnessing the capitalist market dynamics of 'creative-destruction' to advance their transformative green ambitions through green growth. They also assess the implications of developmental environmentalism for developed and developing countries, and the future of the global green shift in an era of geostrategic rivalry.
Keywords: 300; East Asia; green energy shift; creative-destruction; developmental environmentalism; developmental state; Schumpeter; economic statecraft; hybridized industrial ecosystems; green growth